Serum from Varicose Patients Induces Senescence-Related Dysfunction of Vascular Endothelium Generating Local and Systemic Proinflammatory Conditions - Ksiazek, Krzysztof; Krasiński, Zbigniew; Sosińska, Patrycja; Aniukiewicz, Krzysztof; Uruski, Paweł; Mikuła-Pietrasik, Justyna; Tykarski, Andrzej (Oxidative medicine and cellular longevity, 2016)
Although the role of endothelium in varicose vein development is indisputable, the effect of the pathology on biological properties of endothelial cells remains unclear. Here we examined if the presence of varicose veins affects senescence of endothelial cells (HUVECs) and, if so, what will be the local and systemic outcome of this effect. Experiments showed that HUVECs subjected to serum from varicose patients display improved proliferation, increased expression of senescence marker, SA-β-Gal, and increased generation of reactive oxygen species (ROS), as compared with serum from healthy donors. Both increased SA-β-Gal activity and ROS release were mediated by TGF-β1, the concentration of which in varicose serum was elevated and the activity of which in vitro was prevented using specific neutralizing antibody. Senescent HUVECs exposed to varicose serum generated increased amounts of ICAM-1, VCAM-1, P-selectin, uPA, PAI-1, and ET-1. Direct comparison of sera from varicose and healthy donors showed that pathological serum contained increased level of ICAM-1, VCAM-1, P-selectin, uPA, and ET-1. Calendar age of healthy subjects correlated positively with serum uPA and negatively with P-selectin. Age of varicose patients correlated positively with ICAM-1, VCAM-1, and ET-1. Collectively, our findings indicate that the presence of varicose veins causes a senescence-related dysfunction of vascular endothelium, which leads to the development of local and systemic proinflammatory environment.